Effect of exercise on Fibroblast Growth Factor 21 levels in healthy males and females - Matthew Peterson; Kathleen A. Richardson; LesLee Funderburk (PLoS ONE, 2025)
Fibroblast growth factor 21 (FGF21) is a metabolic regulator that may increase in circulation following exercise. This study was undertaken to determine if changes to FGF21 post-exercise are dependent on biological sex and exercise modality. Secondary analyses were conducted to determine if the post-exercise rise in FGF21 was associated with upstream signaling factors (glucagon, epinephrine, glucose) and excess post-exercise oxygen consumption (EPOC) response. Following a randomized crossover design, male and female participants completed two, thirty minute exercise protocols – during the steady state (SS) protocol, participants cycled at 70% of VO2peak and during the sprint interval exercise (IE) protocol participants completed six, thirty second “all out” sprints against 7.5% of body weight with four and half minutes of active recovery between sprints. Blood samples were taken at baseline, immediately post-exercise (IPE), and 1-hour post-exercise. Oxygen consumption was monitored continuously throughout the trials. In males, FGF21 levels were increased at 1-hour post-exercise with no difference between conditions; in females, FGF21 levels were unchanged as a result of exercise. Comparison of the post-exercise FGF21 incremental area under the curve revealed that in the SS condition males had a greater FGF21 response than females and that within males the SS condition had a greater response than the IE condition. Exercise significantly increased FGF21 levels in males, but not in females. In males, FGF21 levels were greater in the SS condition than in the IE condition.